Interactions Among the Fire, Vegetation, the North American Monsoon and the El Niño-Southern Oscillation in the North American Desert Southwest - Brunelle, Andrea (Frontiers in Ecology and Evolution, 2022)
Millennial-scale environmental histories from desert SW ciénegas were examined with existing time series for the North American Monsoon (NAM) and El Niño, in concert with published long-term records of desert vegetation and climate. The goal was to better understand the relationships among the seasonality of climate, effective moisture levels, and vegetation type. It was determined that without sufficient winter precipitation fires are rare in desert SW ecosystems. However, it was also determined that in addition to winter moisture, summer ignitions are critical for fire in southwestern deserts. A relationship between the abundance of woody fuels and charcoal abundance was identified, although further calibration on charcoal production in woody vs. grassy desert settings in necessary to fully understand this interplay. Finally, the impacts of climate change and invasive species were considered, with both likely increasing the frequency of fire in desert ecosystems.